GPS constraints on broad scale extension in the Ethiopian Highlands and Main Ethiopian Rift. Issue 13 (4th July 2016) - Birhanu, Yelebe; Bendick, Rebecca; Fisseha, Shimeles; Lewi, Elias; Floyd, Michael; King, Robert; Reilinger, Robert
Abstract: Measurements from GPS sites spanning the Ethiopian Highlands, Main Ethiopian Rift, and Somali Platform in Ethiopia and Eritrea show that present‐day finite strain rates throughout NE Africa can be approximated at the continent scale by opening on the MER. Most sites in the Ethiopian Highlands are consistent with the motion of the Nubian plate at the level of 1 mm/yr with 95% confidence. However, sites at least as far as 60 km west of the rift show higher velocities relative to the stable Nubian frame of 1–2 mm/yr, requiring a combination of localized and distributed deformation to accommodate the African extensional domain. Off‐rift velocities are consistent with ongoing strain related to either high gravitational potential energy or intrusive magmatism away from midrift magmatic segments either on the western rift margin or within the Ethiopian Highlands, especially when combined with likely rheological differences between the Ethiopian Rift and Highlands. Velocities from the Somali Platform are less well determined with uncertainties and residuals from a Somali frame definition at the level of 2–3 mm/yr but without spatially correlated residuals. Key Points: The Ethiopian Highlands extend African stretching is accommodated by multiple mechanisms The African rift deforms in the same way as other continental regions